Pentingnya Audit Investigasi pada Perusahaan Unicorn Indonesia yang Melakukan Penipuan Investasi - Susanto Susanto; Yoyon Mulyana Darsuman; Muhammad Iqbal (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to analyze in more depth the case of alleged manipulation of eFishery's financial statements, showing the importance of investigative audits in maintaining transparency, accountability, and investor trust. This study uses a normative legal approach to analyze the alleged manipulation case of eFishery's financial statements and the urgency of investigative audits in preventing and prosecuting similar cases in Indonesian unicorn companies. Common fraud schemes include financial statement manipulation, where companies inflate revenue, record fictitious transactions, or conceal debt to create an illusion of profitability. Additionally, Ponzi schemes pose a significant risk to investors, as returns promised to earlier investors are paid using funds from new investors rather than legitimate business profits. Regulations such as Law No. 8 of 1995 on Capital Markets and Law No. 10 of 1998 on Banking require companies raising public funds to provide transparent and accurate financial information. In the case of eFishery, investigative auditing is essential to uncover potential violations of these regulations. Findings from investigative audits can be used by regulators such as OJK, Bappebti, and Kominfo to tighten supervision and take action against companies proven to engage in fraudulent practices. Additionally, investigative auditing plays a preventive role in maintaining investor confidence and ensuring the sustainable, transparent growth of the startup ecosystem.